Challenges of enbloc mid-sacrectomy as redo surgery for sacral chordoma: a case report - Ali, Sundus; Ishaq, Ahtsham; Qasim, Adnan; Muhammad Naeem; Sarwar, Muhammad Rizwan; Shams, Shahzad (Journal of the Pakistan Medical Association, 2024)
Enbloc Sacrectomy is the procedure of choice for aggressive sacral lesions but not widely practiced in Pakistan, both by Neurosurgeons and Orthopaedic surgeons. Only one case has been mentioned in indexed local literature so far and that too not operated in Pakistan. The case of a case of a 27 year old neurologically intact male is presented. He had a huge residual mass and midline non-healing wound after two attempts at intralesional debulking and one full course of local irradiation. He presented to the Mayo Hospital, Lahore on 29th December 2021 for a redo surgery of sacral chordoma. A marginal excision was achieved utilizing posterior only approach. This case will help understanding the key steps in enbloc mid-Sacrectomy and importance of involving multidisciplinary team for ensuring adequate wound closure. Keywords: Sacral chordoma, Mid-Sacrectomy, Enbloc.